«Palmas y guitarra»: physical and spiritual fusion of Vallejo and Georgette - García, Mara L. (2023)
César Vallejo is the most important universal bard that Peru has produced and his work is recognized for its quality and literary originality. This work will have two sections: the first one, «Georgette y Vallejo, almas inseparables», where I will expose indications that Georgette and Vallejo were soul mates destined to live together. They created a «we» shaped with ingredients of loyalty and commitment. It was a love not only linked to the physical and sexual, but both came to form a total unity of body and soul as a couple. While, in the second, «Palmas y guitarra: unión de Georgette y Vallejo», I will make a detailed analysis of the poem «Palmas y guitarra», which the universal bard dedicated to Georgette. In these verses is registered the total union of Georgette and Vallejo, leaving his love and his total identification with the loved one in the verses and images projected in the poem. Vallejo’s lyrical speaker not only claims the body of the beloved, but also demands her abstract part, which has the capacity to feel, love and think. It is the immortal and spiritual part of the woman that represents her totality. The lyrical voice searches for that essence that makes true love flow.